Medical Students’ Perception Towards Online Assessment - Reddy Kasarla, Rajeshwar; Pathak, Laxmi; Yadav, Nikita Singh (Medical Journal of Eastern Nepal, 2024)
Background: Universal College of Medical Sciences (UCMS), Bhairahawa, Nepal conducted online assessment MCQ tests during covid-19 lock down period. This study was taken up to measure/assess the basic science MBBS students’ perception towards online assessment tests.Methods: A descriptive, cross-sectional study was conducted by administering Google Forms questionnaire to basic scinces MBBS students of UCMS during the period the period of 2 October 2021 to 30 December 2021, using non-probability purposive sampling. General information profroma for socio-demography, and a questionnaire on the lines of Likert’s summated rating scale to assess the perception of MBBS basic science students towards online assessment was constructed. Simple frequency tables, cross tables, and mean tables have been used to analyze data. Characteristics of the sample were categorized using mean and standard deviation.Results: The overall mean and standard deviation for perception of online assessment tests were 3.17 and 0.65 respectively. The results indicate that MBBS students were satisfied with online assessment tests.Conclusion: Online assessment tests were well received by MBBS students. The online assessment tests enhance student learning by allowing immediate feedback. Online tests should be conducted in medical colleges on a regular basis.